2020
DOI: 10.1017/s0714980820000318
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation in Long-term Residential Care: Case Studies from Canada, Norway, and Germany

Abstract: Meaningful social engagement in everyday activities can enhance resident quality of life in nursing homes. In this article, we draw on data collected in a multidisciplinary, international study exploring promising practices in long-term care homes across Canada, Norway, and Germany, to investigate conditions that either allow for or create barriers to residents’ social participation. Within a feminist political economy framework using a team-based rapid ethnography approach, observations and in-depth interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
3
29
0
1
Order By: Relevance
“…The proportion of people suffering from dementia will increase from 1.59 million in 2020 to 2.35 million in 2050 [ 6 ]. Since people suffering from dementia have a high care dependency [ 7 ], this growing proportion is expected to be accompanied by an increase in institutional care in the next years [ 2 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The proportion of people suffering from dementia will increase from 1.59 million in 2020 to 2.35 million in 2050 [ 6 ]. Since people suffering from dementia have a high care dependency [ 7 ], this growing proportion is expected to be accompanied by an increase in institutional care in the next years [ 2 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We did not identify a study directly analyzing the impact of staff on the maintenance of everyday life and social contacts. However, Lowndes et al [ 8 ] identified that staff themselves have little to no time for engaging socially with residents and that staff cannot focus enough on residents’ social needs in Canada, Germany, and Norway. Especially during evening shifts that often are understaffed, it seems impossible to enable residents to be socially active [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations